Aqueous leaf extract from Luehea divaricata Mart. Modulates oxidative stress markers in the spinal cord of rats with neuropathic pain. (25th March 2021) - Kroth, Adarly; Santos, Maria do Carmo Quevedo; Borella da Silva, Thaisla Cristiane; Santos Silveira, Elza Maria; Partata, Wania Aparecida
Abstract: Ethnopharmacological relevance: Reactive oxygen species (ROS) play an important role in neuropathic pain (i.e., pain caused by lesion or disease of the somatosensory system). We showed previously that the aqueous extract prepared from Luehea divaricata leaves, a plant explored by native ethnic groups of Brazil to treat different pathologic conditions, exhibits good antioxidant activity and induces analgesia in rats with neuropathic pain (J Ethnopharmacol, 2020; 256:112761. doi: 10.1016/j.jep.2020.112761). The effect was comparable to that of gabapentin, a drug recommended as first-line treatment for neuropathic pain. However, increasing evidence has indicated the need to accurately determine the oxidative stress level of an individual before prescribing supplemental antioxidants. Aim of the study: This study assessed the effects of the oral administration of aqueous extract from leaves of L. divaricata on the sciatic functional index (SFI) and spinal-cord pro-oxidant and antioxidant markers of rats with neuropathic pain. Materials and methods: Placement of four loose chromic thread ligatures around the sciatic nerve produced chronic constriction injury (CCI) of the sciatic nerve, a commonly employed animal model to study neuropathic pain. Aqueous extract from leaves of L. divaricata (100, 300, 500 and 1000 mg/kg), gabapentin (50 mg/kg) and aqueous extract (500 mg/kg) + gabapentin (30 mg/kg) were administrated per gavage daily for 10 or 35 days post-CCI. Antinociception was assessed using the von Frey test while SFI showed functional recovery post-nerve lesion throughout the experimental period. At days 10 and 35 post-surgery, the lumbosacral spinal cord and a segment of the injured sciatic nerve were dissected out and used to determine lipid hydroperoxide levels and total antioxidant capacity (TAC). The spinal cord was also used to determine superoxide anion generation (SAG), hydrogen peroxide (H2 O2 ) levels and total thiol content. Results: As expected, the extract, gabapentin and extract + gabapentin induced antinociception in CCI rats. While no significant functional recovery was found at 10 days post-CCI, a significant recovery was found in SFI of extract-treated CCI rats at 21 and 35 days post-CCI. A significant functional recovery was found already at day 10 post-CCI in gabapentin and gabapentin + extract-treated CCI rats. The extract treatment prevented increases in lipid hydroperoxides levels and TAC in injured sciatic nerve, which were found in this tissue of vehicle-treated rats at 10 days post-CCI. Extract also prevented an increase in SAG, H2 O2 and lipid hydroperoxides levels in the spinal cord, which were elevated in this tissue of vehicle-treated rats at 10 and 35 days post-CCI. Extract also prevented a decrease in total thiol content and an increase in TAC in the spinal cord of CCI rats in these same time periods. Conclusions: Aqueous extract from L. divaricata leaves was demonstrated, for the first time, to improve SFI and modulate oxidative stress markers in injured sciatic nerve and spinal cord of CCI rats. Thus, the antinociceptive effect of the extract involves modulation of oxidative stress markers in injured sciatic nerve and spinal cord. Graphical abstract: Image 1 Highlights: Luehea divaricata induce recovery in sciatic functional index in rats with CCI. Luehea divaricata revert superoxide anion generation increased by CCI in spinal cord. Luehea divaricata revert hydrogen peroxide levels increased by CCI in spinal cord. Extract from leaves of L. divaricata affects oxidant biomarkers in spinal cord.